Evaluasi Penerapan Prinsip Good Governance pada Lembaga Amil Zakat Nurul Fikri Kota Palangka Raya - Khairun Jariyah; Muhammad Noor Sayuti; Hanief Monady; Rofi Rofi (Muttaqien, 2025)
This study examines the implementation of Good Amil Governance (GAG) in zakat management at LAZ Nurul Fikri, Palangka Raya. This study focuses on six main principles: transparency, accountability, responsibility, independence, fairness, and Sharia compliance. The method used is descriptive qualitative, with data collection through semi-structured interviews with key informants, direct observation, and documentation review. Data analysis was conducted using the Miles and Huberman model, including data reduction, presentation, and conclusion drawing. The results show that LAZ Nurul Fikri has significantly implemented GAG principles, especially in transparency and accountability, as reflected in using a digital system for financial reports, routine internal and external audits, and information disclosure to stakeholders. However, responsibility and independence remain due to limited human resources and low public awareness of zakat. Supporting factors include an efficient reporting system and high muzaki participation, while inhibiting factors are a weak collaboration network and poor zakat literacy. This research offers practical implications for zakat institutions, policymakers, and academics, emphasizing the importance of digitalization, human resource development, and strategic collaboration. Future research should conduct cross-regional comparisons and use a mixed-methods approach to strengthen the results.